Development Of Prototype Smart Door System With IoT Application - Norarzemi, Ummi Annisa; Zainal, Mohd Shamian; Abu Hassan, Omar; Zohari, Mohd Hakimi; Md Nor, Danial; Hamzah, Shipun Anuar; Mohamed, Masnani (Progress in Engineering Application and Technology, 2020)
In this paper, the design of prototype Smart Door System with IoT Application which act as a digital door system is discussed. This paper presents the idea of controlling the lock, detecting a motion, and monitoring by live camera via a mobile application. This study is conducted to propose an enhancement to the traditional door system by utilizing the Internet of Things (IoT) technology. The bridge that we built between hardware and Internet is what we call IoT, and in this paper, Blynk application is used as the bridge for IoT.